Determination of distinct morphological differences between carcass of village chicken, color broiler, and white plumage broiler chicken - Shaib, Juliana (2017)
A study was conducted to investigate the morphological differences that exist between three types of chicken which is village chicken, color broiler and broiler chicken. The specific objectives are to determine differences in breast characteristics and other body parts between three types of chicken and to determine differences in skin characteristics between three types of chicken. Three types of chicken were randomly selected form three different sources. Age of chickens were different for every types but had same body weight of 1.5kg. The height of breast bone showed there was significant different (P<0.05) among three types of chicken. The depth for breast muscle showed that village chicken and color broiler was not significant difference (P>0.05), but the white broiler chicken show significant different (P<0.05). There were three parts to measure the skin thickness which are breast, thigh and back part. For the breast part there was no significantly different between color broiler and white broiler. The village chicken skin thickness was significant. The thigh part of the skin thickness showed that white broiler was significant different than village and color broiler. There was significantly different (P<0.05) for skin thickness at the back part for all three types of the chickens. The feathers follicle for village chicken at the breast part was significant (p<0.05) compare to color and broiler. At the thigh part the feathers follicle count for village and color broiler was not significant. There was significant different (p<0.05) for back part of the broiler chicken to color and village chicken. This study indicates that, there are distinct morphological differences between these three types of chickens.